Volcanic Ash and Small Uncrewed Aerial Vehicle (sUAV) Interaction: In-situ Observations and Laboratory Experiments on Aircraft Failure - Brosch, Ermanno (Frontiers in Earth Science, 2022)
The deployment of small uncrewed aerial vehicles (sUAVs) for volcanological applications has grown over the last decade, mainly attributed to the development of affordable, smaller, and versatile platforms. However, the use of sUAVs in active volcanic regions is a challenging operation conducted under extreme environmental conditions. The here reported unsuccessful deployment of an sUAV at Stromboli volcano shows that the aircraft functionality was impaired by airborne volcanic ash, which led to an uncontrolled landing of the aircraft. Laboratory analyses confirmed the presence of volcanic material inside the motors, which is attributed to have caused motor blockage of the sUAV on Stromboli volcano while the aircraft was engulfed by a rising ash plume. Laboratory experiments were conducted to investigate the interaction between volcanic ash and an sUAV motor-propeller assemble. The experiments reproduced the incorporation of ash-sized particles into the motor, proving that volcanic ash can enter the rotating motor while the sUAV is airborne. This shows that ash ingestion into the sUAV at Stromboli volcano resulted in operational failure. These findings shall aid in developing advanced and reliable sUAVs that can extend current deployment opportunities in volcanic environments.